1992
DOI: 10.1007/bf01122802
|View full text |Cite
|
Sign up to set email alerts
|

Lindane-induced modifications to membrane lipid structure: Effect on membrane fluidity after subchronic treament

Abstract: Chronic lindane intoxication by injecting subcutaneously the toxicant, resulted in an altered lipid pattern in rat ventral prostate membranes. An increase of membrane fluidity was also observed using a fluorescence polarization technique. When in vitro experiments were carried out with both treated and untreated rats, an interesting lack of parallelism was found, which could indicate the development of a resistance to membrane disordering by lindane. The observed changes in cholesterol and phospholipid composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This is further strengthened by our observation that incubation of Sertoli cells with U18666A, a hydrophobic amine that induced intracellular cholesterol accumulation, promoted concomitantly intracellular Cx43 delocalization. Owing to its highly lipophilic propriety, it has been proposed that Lindane could insert into the plasma membrane, alter membrane fluidity, and thereby directly modulate the activity of the integrated membrane proteins (15). Consistently, it was demonstrated that a widely used GJIC inhibitor heptanol decreases the fluidity of cholesterol rich domains (52).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is further strengthened by our observation that incubation of Sertoli cells with U18666A, a hydrophobic amine that induced intracellular cholesterol accumulation, promoted concomitantly intracellular Cx43 delocalization. Owing to its highly lipophilic propriety, it has been proposed that Lindane could insert into the plasma membrane, alter membrane fluidity, and thereby directly modulate the activity of the integrated membrane proteins (15). Consistently, it was demonstrated that a widely used GJIC inhibitor heptanol decreases the fluidity of cholesterol rich domains (52).…”
Section: Discussionmentioning
confidence: 94%
“…Although an increasing number of chemicals are able to decrease this cell±cell communication, the underlying mechanism(s) is not identified. It has been proposed that some compounds particularly the lipidsoluble pesticides may disturb the fluidity of the plasma membrane and thereby gap junction channel functions (15).…”
Section: Introductionmentioning
confidence: 99%
“…According to Gutiérrez et al (2000), high concentrations of lindane change the fatty acid composition of pigeon heart microsomes by decreasing the ratios of C18:1n9 and C16:1n7 fatty acids and increasing the percentage of linoleic acid. Due to its highly lipophilic properties, lindane may disturb the fluidity of the plasma membrane (Gutierrez-Ocana et al 1992) and impair gap junction intercellular communication (GJIC) (Defamie et al 2001;Mograbi et al 2003;Loch-Caruso et al 2004). Due to its highly lipophilic properties, lindane may disturb the fluidity of the plasma membrane (Gutierrez-Ocana et al 1992) and impair gap junction intercellular communication (GJIC) (Defamie et al 2001;Mograbi et al 2003;Loch-Caruso et al 2004).…”
Section: Discussionmentioning
confidence: 99%